Small-mammal assemblages inhabiting Sphagnum peat bogs in various regions of Poland - Ciechanowski, Mateusz; Cichocki, Jan; Ważna, Agnieszka; Piłacińska, Barbara (Biological Letters, 2013)
We studied species composition of assemblages of small mammals (rodents and shrews) inhabiting Polish 25 ombrotrophic mires and quaking bogs in several regions in order to reveal characteristic features of their quantitative structure and compare them between regions, internal zones of the bog habitats, and different levels of anthropogenic degradation. We reviewed also all published results of small-mammal trapping in such habitats. Mammals were captured in pitfalls, snap traps and live traps on 12 bogs of the Pomerania region, 4 bogs of the Orawa-Nowy Targ Basin (Kotlina Orawsko-Nowotarska), 3 bogs in the Świętokrzyskie Mts, and 6 bogs in Wielkopolska and the Lubusz Land. Additionally, we included materials collected from Barber traps (pitfalls) used during studies of epigeic invertebrates on 4 bogs. In total, 598 individuals of 12 species were collected. The number of pitfall captures per 100 trapnights was very low (7.0-7.8), suggesting low population density. Shrews predominated among mammals captured in pitfalls, and the assemblage structure appeared to be similar to impoverished forest fauna, slightly enriched with ubiquitous species from meadows and agroecosystems, with a very small percentage of typical wetland species (Neomys fodiens, Neomys anomalus, Microtus oeconomus). Rodents (mostly Myodes glareolus) predominated only in samples obtained by live and snap traps. Pygmy shrew Sorex minutus was the most numerous species at most sites, sometimes being the only small mammal in that habitat, especially in well-preserved, treeless parts of bogs, dominated by Sphagnum peatmoss. The dominance and high constancy of S. minutus appear to be a characteristic feature of small-mammal assemblages inhabiting ombrotrophic mires, at least in some regions of Central and Western Europe. Enrichment of the fauna with other species might be related to either improved trophic conditions (by contact with mineralized ground waters) or habitat degradation (by peat mining, drainage, and subsequent secondary succession).